Identification and sequence analysis of five allexiviruses species infecting garlic crops in Brazil - Oliveira, Milena L. [UNESP]; De Marchi, Bruno R. [UNESP]; Mituti, Tatiana [UNESP]; Pavan, Marcelo A. [UNESP]; Krause-sakate, Renate [UNESP] (Sociedade Brasileira de Fitopatologia, 2014)
Garlic plants are naturally infected by a mixture of viruses, including allexiviruses. Symptomatic garlic plants with mosaic and distorted leaves from garlic producing regions in Brazil were analyzed for the presence of Garlic virus A (GarV-A), Garlic virus B (GarV-B), Garlic virus C (GarV-C), Garlic virus D (GarV-D) and Garlic mite-borne filamentous virus (GarMbFV), five allexivirus species previously reported in the country. Fifty-nine virus isolates from five distinct allexivirus species were identified and the complete coat protein region of each genome was sequenced. Mixed infections were very frequent and corresponded to 43% of the positive samples. The nucleotide identity of the coat protein ranged between 75% and 98% for GarV-A isolates, 83% and 90% for GarV-B, 69% and 98% for GarV-C, 87% and 97% for GarV-D, and 72% and 91% for GarMbFV.
Keywords: Allium sativum; mixed infection; variability; virus